Research on the Input-Output Model in Mexico. Origins and Trends - Aroche Reyes, Fidel (Estudios Económicos de El Colegio de México, 2013)
This paper revises the development and present condition of the InputOutput analysis published in Castilian, from a Mexican viewpoint. The paper combines a historical perspective on the earlier publications and presents some contemporary lines of the applied investigation.